Prevalence and predictors of water pipe (shisha) use among Iranian high school children - Mohammadi, Mahtab; Gyanchand Rampal, Lekhraj Rampal; Mohd Sidik, Sherina; Ibrahim, Normala; Abdul Rahman, Hejar; Ghaleiha, Ali (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2017)
Introduction: Water pipe use is becoming increasingly common among Iranian adolescents. This study examined the prevalence and predictors of water pipe use among public high schoolchildren aged 14-17 in Iran. Methods: A cross-sectional study was conducted among 1st, 2nd and 3rd grade public high schoolchildren in Sanadaj City, capital of Kurdistan province of Iran during the academic year 2012-2013. Cluster sampling was used to select a sample from 8 public high schools. The data were collected using validated self-administrated questionnaire that included questions on water pipe use, socio-demographic characteristics, smoking-related knowledge, attitude toward smoking, normative believes regards perceived prevalence water pipe use among peer and adults, perception of harm, self-esteem and refusal skill. A multivariate logistic regression analysis was performed to assess predictors of water pipe use. Results: A total of 1837 students participated in this study. Students’ ages ranged from 14 to 17 years (mean age±15.09; SD±0.82 years). The overall prevalence of ever water pipe use was 36.2% (43.1% in male and 29.2% in female, (p<0.001). Age, gender, living arrangement, pocket money, academic grade, parental history of smoking, attitude, and normative believes regards perceived prevalence water pipe use among peer and adults were predictors of water pipe use among study participants. Conclusions: The overall prevalence of water pipe is high among high school children in Sanandaj. Age, gender, pocket money, academic grade, parents smoking, attitude toward smoking and normative believes were identified as the most important predictors increasing the risk of water pipe use in the studied students.